ANALISIS KONVERGENSI DAN KETERKAITAN SPASIAL PERTUMBUHAN EKONOMI KABUPATEN/KOTA DI SULAWESI TENGAH - Achmad, Lustiawaty (Katalogis, 2017)
This research aims to analyze the economic growth convergence and spatial dependency in the districts/municipality in Central Sulawesi Province 2010-2014 period. The analysis used panel data regression with Fixed Effect Model and Moran Statistics approach. The results show, firstly no Ïƒ-convergence of economic growth in the districts/municipality in Central Sulawesi over the period. These result indicated by the standard deviation and coefficient of variation per capita GRDP is increasing. Second, there is Î²-convergence conducted by absolute convergence and conditional convergence on economic growth in all district/municipality in Central Sulawesi. Third, life expectancy, mean years of schooling and roads have significant impact on economic growth in the districts/municipality in Central Sulawesi. Fourth, there is no spatial dependency on economic growth among districts/municipality in Central Sulawesi Province.Â